John W. Backus papers - Backus, John W., 1924-2007.
Correspondence, memoranda, speeches, writings, reports, notes, slides, photographs, and other papers relating to Backus's work as a computer scientist at IBM on programming languages, particularly FORTRAN. Includes material relating to Backus's early work on the IBM Selective Sequence Electronic Calculator and Backus-Naur Form (BNF). Documents Backus's pursuit as IBM Fellow, 1963-1991, of his own research projects relating to mathematical theories of programming and the development of functional programming languages. Also includes files pertaining to Backus's political activism as a member of Computer Professionals Against ABM in the early 1970s and as an opponent of the strategic defense initiative in the 1980s.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Computer scientist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Backus, John W., -- 1924-2007 -- Political activity; International Business Machines Corporation; Ballistic missile defenses; Calculators; Computers; FORTRAN (Computer program language); Programming languages (Electronic computers); Computer scientists